The strategic role of fermented foods in enhancing sustainable food security: Integrating policy, nutritional value, and local food system empowerment - Damasetio, Ramzy (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Food security is a fundamental aspect of sustainable development, particularly in Indonesia, which faces challenges such as climate change, land conversion, import dependency, and uneven food distribution. Fermented foods have considerable potential to enhance the sustainability of food security by diversifying food sources, improving nutritional value, and reducing food waste. Previous studies have shown that fermentation processes can extend the shelf life of food products, increase year-round food availability, and support supply stability for communities. In addition, fermented foods contain probiotics and enzymes that benefit digestive health and nutrient absorption, thereby improving the overall nutritional quality of the population. Methods: This study utilizes a literature review to analyze a range of governmental policies and strategies aimed at optimizing the role of fermented foods in national food security. The analysis covers regulatory frameworks, incentives for local producers, and educational initiatives regarding the benefits of fermented food consumption. Findings: The findings indicate that integrating fermented foods into food security policies can promote a more resilient and sustainable food system, reduce reliance on imported products, and empower local small and medium-sized enterprises. There is a positive correlation between increased consumption of fermented foods and both improved nutritional outcomes and economic independence. Conclusion: The integration of fermented foods into national food security strategies may significantly strengthen Indonesia’s capacity to achieve a self-reliant, healthy, and sustainable food system. Novelty/Originality of this article: This article offers a novel perspective on the strategic role of fermented foods in enhancing sustainable food security in Indonesia by synthesizing policy analysis and current trends, an area that has not been extensively addressed in previous research.